1977
DOI: 10.1144/gsjgs.134.1.0041
|View full text |Cite
|
Sign up to set email alerts
|

Precambrian gneisses in the Dalradian sequence of northeast Scotland

Abstract: I n this note we draw attention to data which may require major revision of Dalradian stratigraphy and structure in northeast Scotland. The Central Highland sequence of the Dalradian and the Keith Division ( Read 1955 ) of Banffshire are separated from the metasediments of the Banff Division by gneisses. These are referred to as the Cowhythe Gneiss ( Read 1923 ), Queens Hill Gneiss (Harris & Pitcher 1975), Donside and Ellon Gneiss ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 7 publications
2
29
1
Order By: Relevance
“…Although some authors have also suggested that parts of the area are allochthonous (Sturt et al, 1977;Ramsay and Sturt, 1979), most current interpretations have attempted to correlate the stratigraphical succession in broad terms (i.e. at subgroup level) with Argyll and Southern Highland group successions farther to the south-west (Harris and Pitcher, 1975;Ashworth, 1975;Harte, 1979;Treagus and Roberts, 1981;Ashcroft et al, 1984;Fettes et al, 1991;Harris et al, 1994;Stephenson and Gould, 1995).…”
Section: Stephenson Jr Mendum and Dj Fettesmentioning
confidence: 99%
See 4 more Smart Citations
“…Although some authors have also suggested that parts of the area are allochthonous (Sturt et al, 1977;Ramsay and Sturt, 1979), most current interpretations have attempted to correlate the stratigraphical succession in broad terms (i.e. at subgroup level) with Argyll and Southern Highland group successions farther to the south-west (Harris and Pitcher, 1975;Ashworth, 1975;Harte, 1979;Treagus and Roberts, 1981;Ashcroft et al, 1984;Fettes et al, 1991;Harris et al, 1994;Stephenson and Gould, 1995).…”
Section: Stephenson Jr Mendum and Dj Fettesmentioning
confidence: 99%
“…Some structural and Rb-Sr geochronological evidence has been interpreted to infer that the Cowhythe Psammite Formation, along with all the other gneissose units of the North-east Grampian Highlands, represents a pre-Caledonian Neoproterozoic basement gneiss complex (Sturt et al, 1977). Ramsay and Sturt (1979) suggested that all the rocks above the Portsoy Thrust constitute an allochthonous block, and that this consists of a gneissose basement separated from a Dalradian metasedimentary cover by a décollement along Read's Boyne Line.…”
Section: Major Dislocationsmentioning
confidence: 99%
See 3 more Smart Citations